Comparison of the Complications in Vertical Rectus Abdominis Musculocutaneous Flap with Non-Reconstructed Cases after Pelvic Exenteration - Jeon, Heechang (Arch Plast Surg, 2014)
BACKGROUND: Perineal reconstruction following pelvic exenteration is a challenging area in plastic surgery. Its advantages include preventing complications by obliterating the pelvic dead space and minimizing the scar by using the previous abdominal incision and a vertical rectus abdominis musculocutaneous (VRAM) flap. However, only a few studies have compared the complications and the outcomes following pelvic exenteration between cases with and without a VRAM flap. In this study, we aimed to compare the complications and the outcomes following pelvic exenteration with or without VRAM flap coverage. METHODS: We retrospectively reviewed the cases of nine patients for whom transpelvic VRAM flaps were created following pelvic exenteration due to pelvic malignancy. The complications and outcomes in these patients were compared with those of another nine patients who did not undergo such reconstruction. RESULTS: Flap reconstruction was successful in eight cases, with minor complications such as wound infection and dehiscence. In all cases in the reconstructed group (n=9), structural integrity was maintained and major complications including bowel obstruction and infection were prevented by obliterating the pelvic dead space. In contrast, in the control group (n=9), peritonitis and bowel obstruction occurred in 1 case (11%). CONCLUSIONS: Despite the possibility of flap failure and minor complications, a VRAM flap can result in adequate perineal reconstruction to prevent major complications of pelvic exenteration.